2018
DOI: 10.1101/471912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inherited defects in natural killer cells shape tumor immune microenvironment, clinical outcome and immunotherapy response

Abstract: 27Tumor immune microenvironment (TIME) plays an important role in metastasis and 28 immunotherapy. However, it has been not much known how to classify TIMEs and how TIMEs are 29 genetically regulated. Here we showed that tumors were classified into TIME-rich, -intermediate and -30 poor subtypes which had significant differences in clinical outcomes, abundances of tumor-infiltrating 31 lymphocytes (TILs), degree of key immune programs' activation, and immunotherapy response across 32 13 common cancer types (n= … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…It was shown that MYC is a direct downstream target for sensors involved in antitumor response of NK cells in vivo, endoplasmic reticulum stress sensor inositol-requiring enzyme 1 (IRE1α) and its substrate transcription factor X-boxbinding protein 1 (Han Dong et al, 2019). These findings are in line with the previously made speculations that inheritable defect of two key antitumor activities of NK cells-cytotoxicity and immune cell recruitment-results in low-efficient cancer immunosurveillance and a high risk of tumour development and formation of metastases (Sibbitt et al, 1984;Xu et al, 2018). Thus, it is reasonable to conclude that MYC influences the Elimination phase of immunoediting, affecting innate immunity in both cancer cell-dependent manner (via CD47-dependent mechanisms) and innate cells-intrinsic manner.…”
Section: Granting Cancer To Escape Immunosurveillancesupporting
confidence: 89%
“…It was shown that MYC is a direct downstream target for sensors involved in antitumor response of NK cells in vivo, endoplasmic reticulum stress sensor inositol-requiring enzyme 1 (IRE1α) and its substrate transcription factor X-boxbinding protein 1 (Han Dong et al, 2019). These findings are in line with the previously made speculations that inheritable defect of two key antitumor activities of NK cells-cytotoxicity and immune cell recruitment-results in low-efficient cancer immunosurveillance and a high risk of tumour development and formation of metastases (Sibbitt et al, 1984;Xu et al, 2018). Thus, it is reasonable to conclude that MYC influences the Elimination phase of immunoediting, affecting innate immunity in both cancer cell-dependent manner (via CD47-dependent mechanisms) and innate cells-intrinsic manner.…”
Section: Granting Cancer To Escape Immunosurveillancesupporting
confidence: 89%
“…Since the revealed defects of NK cells in cancer patients do not depend on stage of disease, localization, and metastatic spread, these defects rather precede cancer development than are the result of tumor growth. In line with this, recent “-omic” data (tumor RNA-seq (RNA sequencing) and whole-exome sequences of germline genomes) of The Cancer Genome Atlas of cancer patients ( n = ~6,000) representing 13 common cancer types suggest that individuals who have inherited defects in NK cells experience a high risk of developing cancers [32]. Specifically, in all most common cancers, defects of the NK-specific-genes (i.e., NKD+ NK cell receptors) alone were sufficient to establish the critical correlations with patient survival and tumor infiltration by cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 87%
“…The authors speculate that inheritable defected of two key antitumor activities of NK cells—cytotoxicity and immune cell recruitment—results in low-efficient cancer immunosurveillance and high risk of tumor development and formation of metastases. The authors propose that “cancer is largely a disease of NK cell deficiencies” [32].…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of our study focused on classifying tumor immune microenvironments (TIMEs). Interestingly, we were able to classify TIMEs into three distinct groups commonly found in all cancer types: TIME-rich (or 'immunehot' tumors), TIME-intermediate (or 'immune-cold' tumors) and TIME-poor (or 'immune-desert tumors') [10]. By comparing germline genomics of the three TIME groups, we found that the number of inherited defected NK-cell related genes was negatively correlated with patient survival, TIL abundance in TIMEs, suggesting that inherited defects in NK cells alone were sufficient to shape TILs recruitment and therefore, clinical outcome and immunotherapy response.…”
Section: Germline Implications In the Immune Systemmentioning
confidence: 97%
“…We have shown that inheritably functional variants of breast cancer patients significantly predicted tumor recurrence [7,8], and the risk of developing breast, brain and other cancers [9]. Furthermore, we have shown that inheritably functional variants in natural killer cells (i.e., natural killer [NK] cells, an immune cell type) in cancer patients affected tumor-infiltrating lymphocytes (TILs) and survival [10]. These results bring a paradigm-shifting view about the roles of germline genomes in cancer.…”
mentioning
confidence: 99%